Sistem Pendistribusian Zakat oleh Baznas Kabupaten Langkat Menurut Undang-undang No. 23 Tahun 2011 tentang Pengelolaan Zakat: Studi Kasus di Desa Karang Rejo, Kec. Stabat, Kab. Langkat - Suhairi, Mhd Arbi Bayu; Iqbal, Muhammad Nur; Nasution, Abdul Halim (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
UU no. 23 of 2011 concerning zakat management as a complement to the previous law, namely law no. 38 of 1999. This law provides institutional strengthening in integrated zakat management into a unified integrated system. In turn, the National Amil Zakat Agency becomes the only institution holding zakat authority, and the Amil Zakat Institution as a partner in assisting the National Amil Zakat Agency, as well as government oversight as a regulator. The research aims to answer the problem of how the distribution of zakat according to zakat law no. 23 of 2011 in Kab. Langkat. How is the zakat distribution system by BAZNAS Langkat Regency in Karang Rejo Village. What are the factors causing the delays of the BAZNAS distribution system in Langkat Regency. What is the strategy of BAZNAS Langkat Regency to increase the collection and effectiveness in distributing zakat in Karang Rejo Village, Langkat Regency. This research is a qualitative research using a legal sociology approach. The types of data used in this study are primary data and secondary data, secondary data as initial data obtained from primary and secondary legal materials, then followed by primary data or field data obtained from documents and interviews with several Amil Agency officials Langkat District National Zakat. The results of the study show that the National Amil Zakat Agency in Langkat Regency has not run optimally in the distribution of zakat due to several obstacles, one of which is the lack of synergy with the local government in terms of regulations that have an impact on non-optimal distribution.